Analgesic and Sedative Effects of Different Doses of Dexmedetomidine Combined with Butorphanol in Continuous Analgesia after a Cesarean Section - Liu, Hui; Wang, Yalin; Li, Fulong; Ren, Wei; Yuan, Li (Frontiers in Surgery, 2022)
Objective: The present study is designed to study the analgesic and sedative effect of different dose of dexmedetomidine combined with butorphanol in continuous analgesia after cesarean section. Methods: 60 puerpera undergoing caesarean section were recruited from a single center were divided into 3 groups according to the postoperative continuous analgesia protocol, Control group ( 100 mL normal saline containing 10 μg/kg fentanyl and 0.25 mg palonosetron, 2 ml/h for continuous analgesia for 48 h), DB1 group (100 mL normal saline containing 1.0μg/kg dexmedetomidine, 4 mg butorphanol, 10 μg/kg fentanyl and 0.25 mg palonosetron, 2 ml/h for continuous analgesia for 48 h) and DB2 group (100 mL normal saline containing 2.0μg/kg dexmedetomidine, 4 mg butorphanol, 10 μg/kg fentanyl and 0.25 mg palonosetron, 2 ml/h for continuous analgesia for 48 h). We compared the blood pressure, heart rate, oxygen saturation, VAS score, Ramsay score and adverse reactions of puerpera among the three groups after surgery. Results: Compared with Control group, the systolic blood pressure, diastolic blood pressure, heart rate and VAS score of the puerpera in DB1 group and DB2 group were significantly decreased at 6, 24 and 48 hours (P<0.05), while the Ramsay score the puerpera in DB1 group and DB2 group were significantly increased at 6, 24 and 48 hours (P<0.05), and there is no significant difference in oxygen saturation and adverse reactions of puerpera among the three groups after surgery (P>0.05). At the same time, the the systolic blood pressure, diastolic blood pressure, heart rate and VAS score of the puerpera in DB2 group were significantly lower than those in DB1 group (P<0.05), while the Ramsay score the puerpera in DB2 group were significantly higher than those in DB1 group (P<0.05). Conclusion: Dexmedetomidine combined with butorphanol can improve the analgesic and sedative effects in continuous analgesia after cesarean section, and the analgesic and sedative effects of dexmedetomidine high-dose group are better than low-dose group.